2006
DOI: 10.1111/j.1525-1470.2006.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Childhood Vitiligo in China: An Analysis of 541 Patients

Abstract: From July to December 2002, we collected data from 2247 vitiligo patients in order to establish the clinical and epidemiologic profile of vitiligo in China. Of these patients, 541 (24.1%) were children aged equal to or less than 12 years. Of the 541 children, 274 (50.6%) were boys and 267 (49.4%) were girls, with a mean age of 8.87 years and a mean onset age of 7.28 years. Similar to adult patients, boys and girls were affected by vitiligo with equal frequency. The most frequent age of onset was between 4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
71
5
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 16 publications
23
71
5
6
Order By: Relevance
“…Our review show a preponderance of girls in children with vitiligo, similar to the observation made in majority of previously reported studies [6][7][8][9]10]. Although, two studies from Korea and China noted an almost equal incidence in boys and girls [2,11,12].…”
Section: Discussionsupporting
confidence: 91%
“…Our review show a preponderance of girls in children with vitiligo, similar to the observation made in majority of previously reported studies [6][7][8][9]10]. Although, two studies from Korea and China noted an almost equal incidence in boys and girls [2,11,12].…”
Section: Discussionsupporting
confidence: 91%
“…Studies that reported vitiligo is more common in females: India (Handa &Dogra, 2003, Jaisankar et al, 1992, Kuwait (Nanda et al, 1999), Croatia (Prcic et al, 2006), China (Lin et al, 2011), differed from our data. The mean age (11 years old) of our cohort was higher than other reports (between 6.2 years to 9 years) (Handa & Dogra, 2003, Hu et al, 2006, Nanda et al, 1999, Prcic et al, 2006. A family history of vitiligo (about 20%) was comparable to those of Akrem's (18%) (Akrem et al, 2008), but higher than of Lin's (Lin et al, 2011) (13.5%).…”
Section: Discussioncontrasting
confidence: 49%
“…However boys and girls were affected equally in Zhi Hu et al study. 17 In our study, the commonest age of onset of the disease was between 4 to 9 years constituting 77.5% of the cases. Belliappa et al reported that 68.9% of cases had onset of disease between 4 and 8 years of age similar to our study.…”
Section: Discussionmentioning
confidence: 99%